"Ministering at the Altar of Slavery": Religious slavery conflict and social movement repression. Issue 2 (11th April 2023) - George, Kristin
Abstract: Why did some American Protestant denominations experience slavery-related schism during the nineteenth century, while others appear to have been unaffected by slavery conflict? I conduct a comparative case study of four national Protestant denominations and find that slavery-related schism was not a consequence of a particular theological orientation, but instead occurred when denominational leaders lacked the capacity to repress abolitionism. In all four denominations, leaders attempted to stifle the abolition movement to avoid conflict. Their capacities to do so differed, however: in some denominations, diffusely distributed authority created openings for abolitionist mobilization, eventually leading to irreconcilable conflict and schism. In other denominations, concentrated authority enabled repression, leaders blocked abolitionist mobilization, and schism was avoided. This research shows that non-state targets of social movements can use "soft" forms of repression to undermine movement mobilization, but that their capacity to do so is constrained by organizational characteristics. It also demonstrates the critical role of organizational dynamics in shaping religious responses to contentious issues more broadly.